2018
DOI: 10.1007/s11663-018-1215-x
|View full text |Cite
|
Sign up to set email alerts
|

A XANES Study of Sulfur Speciation and Reactivity in Cokes for Anodes Used in Aluminum Production

Abstract: Availability of anode raw materials in the growing aluminum industry results in a wider range of petroleum cokes being used to produce carbon anodes. The boundary between anode grade cokes and what previously was considered non-anode grades are no longer as distinct as before, leading to introduction of cokes with higher sulfur and higher trace metal impurity content in anode manufacturing. In this work, the chemical nature of sulfur in five industrial cokes, ranging from 1.42 to 5.54 wt pct S, was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In CPC in some cases sulfur has been observed as a thiophene-containing polycyclic aromatic hydrocarbons [12][13][14][15]. In the high sulfur cokes studied here for metal impurities, a previous study has shown that the sulfur is present as elemental sulfur or at least contains S-S bonds [16]. These cokes did not follow the normally accepted trend of decreasing CO2 reactivity with increasing sulfur content.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…In CPC in some cases sulfur has been observed as a thiophene-containing polycyclic aromatic hydrocarbons [12][13][14][15]. In the high sulfur cokes studied here for metal impurities, a previous study has shown that the sulfur is present as elemental sulfur or at least contains S-S bonds [16]. These cokes did not follow the normally accepted trend of decreasing CO2 reactivity with increasing sulfur content.…”
Section: Introductionmentioning
confidence: 62%
“…1% of the total sulfur in the coke. The dominant form of the S in coke is not sulfide, but appears to be organic or S-S bound sulfur [16].…”
Section: Sulfur Chemistry In Cokesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the sulfur content of the carbon anode is increasing day by day, so S emission is very difficult to control. [ 10–13 ] These factors cause the workshop to release more PFC gas and SO 2 gas. [ 14 ] According to international standards, as the main component of PFC gas, CF 4 has a greenhouse effect 6500 times that of CO 2 , while SO 2 damages the environment and endangers human health.…”
Section: Introductionmentioning
confidence: 99%
“…This will not necessary represent industrially produced anodes, as doped anodes may not have the same chemical state properly incorporated within the coke structure, which may give misleading results compared to the industrial cokes. Sulfur speciation of selected cokes was previously performed by the authors by the X-ray absorption near-edge structure (XANES) technique [7]. Five cokes were investigated, which varied significantly with respect to content of sulfur (1.4 to 5.5 wt%) and content of metal impurities.…”
Section: Introductionmentioning
confidence: 99%